Clinical benefit of additional whole-exome sequencing over panel sequencing in an all-comer real-world molecular tumor board - Krieghoff-Henning, Eva; Michaeli, Christoph T.; Boch, Tobias; Kirchhof, Janna; Haselmann, Verena; Neumaier, Michael; Hofmann, Wolf-Karsten; Betge, Johannes; Ebert, Matthias; Teufel, Andreas; Ast, Volker; Sauer, Christian; et al. (ESMO open, 2025)
Background - Panel sequencing, whole-exome sequencing (WES) and whole-genome sequencing (WGS) often uncover therapeutic targets for cancer patients. However, it is still largely unclear to what extent patients directly benefit from broader analyses over panel sequencing alone. - Materials and methods - We analyzed the molecular findings and recommendations issued by our molecular tumor board (MTB) in a cohort of patients who had received both a well-established diagnostic panel of medium size (up to 203 genes) and in-house WES, focusing on the number of recommendations that were issued on the basis of WES results only. - Results - Our cohort consisted of 38 patients with advanced cancers, of whom about two-thirds had common and one-third had rare cancers. They received a total of 45 (range 0-4) treatment recommendations overall, of which 29 had a clinical level of evidence (LoE) and/or entailed a feasible study enrollment and were thus considered highly actionable. Sixteen recommendations, of which seven were highly actionable, were issued only on the basis of WES results (five own, two previous WES). Three out of those seven recommendations and one additional recommendation based on a previous large panel were related to complex molecular biomarkers such as homologous recombination deficiency or high tumor mutational burden, with poly (ADP-ribose) polymerase inhibitors or checkpoint inhibitors as recommended treatment. As expected, a higher proportion of the WES-only recommendations (63% versus 42% of recommendations overall) were based on non-clinical LoEs. One of eight recommendations implemented so far was based on biomarkers derived by WES only. - Conclusions - In our MTB, WES enabled some additional clinically highly actionable recommendations for selected patients, suggesting that some patients do benefit from additional WES. These recommendations were often related to complex biomarkers, which may in principle also be derived from larger panels. These findings should be re-investigated prospectively in larger cohorts.